Origin and Impact of Nitric Oxide in Pseudomonas aeruginosa Biofilms - Cutruzzolà, Francesca (J Bacteriol, 2015)
The formation of the organized bacterial community called biofilm is a crucial event in bacterial physiology. Given that biofilms are often refractory to antibiotics and disinfectants to which planktonic bacteria are susceptible, their formation is also an industrially and medically relevant issue. Pseudomonas aeruginosa, a well-known human pathogen causing acute and chronic infections, is considered a model organism to study biofilms. A large number of environmental cues control biofilm dynamics in bacterial cells. In particular, the dispersal of individual cells from the biofilm requires metabolic and morphological reprogramming in which the second messenger bis-(3′-5′)-cyclic dimeric GMP (c-di-GMP) plays a central role. The diatomic gas nitric oxide (NO), a well-known signaling molecule in both prokaryotes and eukaryotes, is able to induce the dispersal of P. aeruginosa and other bacterial biofilms by lowering c-di-GMP levels. In this review, we summarize the current knowledge on the molecular mechanisms connecting NO sensing to the activation of c-di-GMP-specific phosphodiesterases in P. aeruginosa, ultimately leading to c-di-GMP decrease and biofilm dispersal.